2017
DOI: 10.1002/2017gl076188
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Soil Carbon Dynamics Expressed at the Molecular Level

Abstract: The stability and potential vulnerability of soil organic matter (SOM) to global change remain incompletely understood due to the complex processes involved in its formation and turnover. Here we combine compound‐specific radiocarbon analysis with fraction‐specific and bulk‐level radiocarbon measurements in order to further elucidate controls on SOM dynamics in a temperate and subalpine forested ecosystem. Radiocarbon contents of individual organic compounds isolated from the same soil interval generally exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 70 publications
5
33
0
Order By: Relevance
“…Many previous investigations have uncovered evidence for annual to multi-millennial residence times for lipids and bulk OC in soils (e.g., Harrison, 1996;Tegen and Dörr, 1996;Rethemeyer et al, 2004;Smittenberg et al, 2006;Hilton et al, 2015;Van der Voort et al, 2017). Smittenberg et al (2006) found that soil redevelopment following glacial retreat in British Columbia was accompanied by a steady increase in the age of higher plant alkanes accumulating in Saanich Inlet sediments over the Holocene.…”
Section: Analysis and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous investigations have uncovered evidence for annual to multi-millennial residence times for lipids and bulk OC in soils (e.g., Harrison, 1996;Tegen and Dörr, 1996;Rethemeyer et al, 2004;Smittenberg et al, 2006;Hilton et al, 2015;Van der Voort et al, 2017). Smittenberg et al (2006) found that soil redevelopment following glacial retreat in British Columbia was accompanied by a steady increase in the age of higher plant alkanes accumulating in Saanich Inlet sediments over the Holocene.…”
Section: Analysis and Implicationsmentioning
confidence: 99%
“…Organic matter storage within, and transfer between, intermediate pools (e.g., soils or floodplain sediments) likely exerts a strong influence on the overall timescales of transmission of OC from biological source to sedimentary sink, the nature of exported OM as well as the overall efficiency of OC translocation. The non-contemporary (aged, or "pre-aged") radiocarbon signatures (i.e., 14 C age older than 1950) of certain DOC and especially POC fractions in an array of soils (Trumbore and Harden, 1997;Lichtfouse, 1999;Rethemeyer et al, 2004;van der Voort et al, 2017), rivers and estuaries (Raymond and Bauer, 2001;Goñi et al, 2005;Galy & Eglinton, 2011;Tao et al, 2015), and oceanic settings proximal to continental margins (Goñi et al, 2005;Walker et al, 2014;Blair et al, 2004;Drenzek et al, 2007;Griffith et al, 2010;Tao et al 2016;Bröder et al, 2018) must at least partly reflect these storage and transport times. However, such 14 C depletions may also reflect the presence of petrogenic material weathered from ancient sedimentary rocks that has resisted complete destruction by diagenetic and catagenetic forces for millions of years (Yunker et al, 2002;Goñi et al, 2005;Drenzek et al, 2007;Galy et al, 2008;Hilton et al, 2011;Van der Voort et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This apparent shift in the loci and nature of soil mobilization is also accompanied by a 3-fold increase in sediment flux (Pradhan et al, 2014), implying extensive soil loss from the upper catchment (e.g. Van Oost et al, 2012). This loss may have stemmed from both natural (aridification and associated reduction in vegetation cover) and anthropogenic (agriculture and irrigation) causes, the latter potentially being triggered by changes in regional climate.…”
Section: Linkages Between Godavari Drainage Basin and Marine Sedimentmentioning
confidence: 98%
“…This is particularly so for subtropical river basins of central Asia, where the influence of anthropogenic activity on the landscape and watersheds extends back several millennia (e.g. Van Oost et al, 2012). Within the past 2 centuries, humans have imparted particularly dramatic changes on drainage basins both in terms of land use (e.g.…”
Section: Linkages Between Godavari Drainage Basin and Marine Sedimentmentioning
confidence: 99%